Biological assessment of bisphenol A degradation in water following direct photolysis and UV advanced oxidation - Chen, Pei-Jen; Linden, Karl G.; Hinton, David E.; Kashiwada, Shosaku; Rosenfeldt, Erik J.; Kullman, Seth W. (Chemosphere (Oxford), 2006)
Endocrine disrupting compounds (EDCs) are exogenous environmental chemicals that can interfere with normal hormone function and present a potential threat to both environmental and human health. The fate, distribution and degradation of EDCs is a subject of considerable investigation. To date, several studies have demonstrated that conventional water treatment processes are ineffective for removal of most EDCs and in some instances produce multiple unknown transformation products. In this study we have investigated the use of direct photolysis with low-pressure (LP) Hg UV lamps and UV + hydrogen peroxide (H 2O 2) advanced oxidation process (AOP) for the degradation of a prototypic endocrine disrupter, bisphenol A (BPA), in laboratory water. Removal rates of BPA and formation of degradation products were determined by high performance liquid chromatography (HPLC) analysis. Changes in estrogenic activity were evaluated using both in vitro yeast estrogen screen (YES) and in vivo vitellogenin (VTG) assays with Japanese medaka fish ( Oryzias latipes). Our results demonstrate that UV alone did not effectively degrade BPA. However, UV in combination with H 2O 2 significantly removed BPA parent compound and aqueous estrogenic activity in vitro and in vivo. Removal rates of in vivo estrogenic activity were significantly lower than those observed in vitro, demonstrating differential sensitivities of these bioassays and that certain UV/AOP metabolites may retain estrogenic activity. Furthermore, the UV/H 2O 2 AOP was effective for reducing larval lethality in treated BPA solutions, suggesting BPA degradation occurred and that the degradation process did not result in the production of acutely toxic intermediates.